Another brick on the wall: On the effects of non-contributory pensions on material and subjective well being - Rosangela Bando Grana; Sebastián Galiani; Paul J. Gertler (Inter-American Development Bank (IDB), 2021)
Public expenditures on non-contributory pensions are equivalent to at least 1 percent of GDP in several countries in Latin America and is expected to increase. We explore the effect of non-contributory pensions on the well-being of the beneficiary population by studying the "Pensiones Alimentarias" program established by law in Paraguay, which targets older adults living in poverty. Households with a beneficiary increased their level of consumption by 44 percent. The program improved subjective well-being in 0.48 standard deviations. These effects are consistent with the findings of Bando, Galiani and Gertler (2020) and Galiani, Gertler and Bando (2016) in their studies on the non-contributory pension schemes in Peru and Mexico. Thus, we conclude that the effects of non-contributory pensions on well-being in Paraguay are comparable to those found for Peru and Mexico and add to the construction of external validity.
Keywords: H4; H3; I1; I3; 330; Non-contributory pensions; poverty; mental health and wellbeing